Comparison of Anticipation Accuracy and Visual Search Behavior of Handball Players in Simulated Triple Handball Defense Situation - Zahra Nezakat-Alhosseini; Saleh Rafiee; Sadegh Nasri (Vesnu Publications, 2020)
Introduction: The purpose of this study is to compare the anticipation accuracy and visual search behavior of handball players in three different defensive positions of 1 × 1, 2 × 2, and 3 × 3.Materials and Methods: In this study, 20 handball players aged 16-19 from among national youth team and Pishgaman team of Isfahan, Iran, and were selected via purposive sampling method. At first, videos of different game situations were recorded by the researcher in three situations (1 × 1, 2 × 2, and 3 × 3). Then, handball players observed the three attack-defense positions by eye-tracking device. Then, the players' anticipation of the outcome of the ball position (Fint, Shot, Pass) that was told verbally, was recorded by the researcher and the players' visual search behavior was recorded by the eye-tracker.Results: The result of repeated measures analysis of variance (ANOVA) and Bonferroni post hoc test illustrated that there was a significant different in the anticipation, number, and total duration of visual fixation of the skilled players in the three situations. The anticipation, number, and duration of fixation in the 3 × 3 position were better than the two other positions (P = 0.05). The players looked at the opponent's head, trunk, and hands for position recognition.Conclusion: In the present study, defensive handball players focused on the background information on the player's head, trunk, and hand in order to anticipate and identify the attacking player's pattern in position three versus three relative to position two versus two in position two and position one in front of one. In addition, the visual search behavior in position three versus three was better for the player than the other two positions.